Des jeux d'alliances éducatives sur un territoire rural. Une étude d'impact dans le cadre de la réforme des rythmes scolaires - Karine Bonnaud (Nantes Université, 2023)
This article proposes to shed light on the games of educational alliances at work during the implementation of the 2013 reform of school rhythms in rural areas. Based on an impact study as a change management approach and the framework for analyzing the sensitivity of the shared educational territory, we seek to understand how and how educational alliances are created or not and if so, to what degree and for what sustainability. Our results reveal alliances that are graduated and have more or less porous borders depending on the territorial scale considered. We conclude with prospective elements as to the future of these alliances in view of the pandemic situation to outline a horizon in favour of a desirable local educational future. Résumé en anglais incomplet